Deslizes do discurso jornalístico: Veja e os efeitos de sentido sobre a educação nacional. - Voigt, Juliana Karina (2011)
Based on the French Discourse Analysis approach, initiated by the french philosopher Michel Pêcheux, in 1960, aims to analize the meaning effects generated in the education sessions of Veja magazine, during two different presidential period. We work with discoursive sequences, taken from reports, set in the education sessions to, through the linguistic materiality, be possible investigate the meaning production in this magazine. As is known, Veja is Brazil's best-selling and the fourth best-selling worldwide. For this feature, presents itself in a privileged place with regard to the public formation of opinion, either in the country, either as a reference to foreign nations. Calls itself "Indispensable for the country we want to be" Veja constructs their reality and contributes to the constitution of the social imaginary, camouflaged in the idea of being a weekly news magazine that is there to serve the reader. But the magazine, inserted in the Journalistic Discourse, operates in the meaning institutionalization and contributes to the crystallization of the memory of the past and also to build the memory of the future. That is, the magazine serves as an important tool to promote its crystallized values. What could be observed by negative paraphrases about Brazilian‟s educational system. Negative sense already solidified in the national imaginary. Thus, based on discourse analysis, which cares with the possible interpretations gestures and with the externality of the statements, in the Journalistic Discourse as a discourse on, it is a relevance research to understand how the media, here reduced to Veja magazine, builds its discourse and maintains its positions. To do this study were used, among others authors, Pêcheux (1993), (1995), (1997), (1998); Orlandi (1981), (1996), (2001), (2005), (2006), (2008); Mariani (1998), (1999), (2003), (2006), (2008) e Ferreira (2003), (2005), (2008).